How do you find #lim (sqrt(x^2+1)-1)/(sqrt(x+1)-1)# as #x->0# using l'Hospital's Rule or otherwise?
In our case
By signing up, you agree to our Terms of Service and Privacy Policy
Using L'Hôpital's Rule, differentiate the numerator and denominator separately with respect to ( x ) and then evaluate the limit again.
First, differentiate the numerator: [ \lim_{x \to 0} \frac{d}{dx}(\sqrt{x^2+1}-1) = \lim_{x \to 0} \frac{\frac{1}{2\sqrt{x^2+1}}\cdot 2x}{\frac{1}{2\sqrt{x+1}}} ]
Next, differentiate the denominator: [ \lim_{x \to 0} \frac{d}{dx}(\sqrt{x+1}-1) = \lim_{x \to 0} \frac{\frac{1}{2\sqrt{x+1}}}{\frac{1}{2\sqrt{x+1}}} ]
Now, evaluate the limit again: [ \lim_{x \to 0} \frac{\frac{1}{2\sqrt{x^2+1}}\cdot 2x}{\frac{1}{2\sqrt{x+1}}} = \lim_{x \to 0} \frac{x}{\sqrt{x^2+1}} ]
Since this is an indeterminate form ( \frac{0}{0} ), apply L'Hôpital's Rule once more: [ \lim_{x \to 0} \frac{d}{dx}\left(\frac{x}{\sqrt{x^2+1}}\right) = \lim_{x \to 0} \frac{\sqrt{x^2+1} - \frac{x^2}{\sqrt{x^2+1}}}{(x^2+1)^{3/2}} ]
Simplify the expression: [ \lim_{x \to 0} \frac{\frac{1}{\sqrt{x^2+1}} - \frac{x^2}{(x^2+1)^{3/2}}}{(x^2+1)^{3/2}} = \lim_{x \to 0} \frac{1-x^2}{(x^2+1)^2} ]
Now, substitute ( x = 0 ) into the expression: [ \lim_{x \to 0} \frac{1-x^2}{(x^2+1)^2} = \frac{1-0^2}{(0^2+1)^2} = \frac{1}{1} = 1 ]
Therefore, ( \lim_{x \to 0} \frac{\sqrt{x^2+1}-1}{\sqrt{x+1}-1} = 1 ).
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- Using the definition of convergence, how do you prove that the sequence #limit (sin n)/ (n) = 0# converges from n=1 to infinity?
- How do you determine the convergence or divergence of #Sigma ((-1)^(n+1))/(2n-1)# from #[1,oo)#?
- How do you determine whether the sequence #a_n=n!-10^n# converges, if so how do you find the limit?
- How do you know if the series #(1+n+n^2)/(sqrt(1+(n^2)+n^6))# converges or diverges for (n=1 , ∞) ?
- How do you use basic comparison test to determine whether the given series converges or diverges for #sum n/sqrt(n^2-1)# from n=2 to #n=oo#?
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7